1981
DOI: 10.1530/acta.0.0980428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of lactation on oral glucose tolerance in the puerperium

Abstract: The influence of endogenous hyperprolactinaemia on oral glucose tolerance in normal women post-partum was studied. An oral glucose tolerance test (OGTT) was performed 8 weeks after delivery in 23 women, 13 of whom were breastfeeding. The lactating women had significantly higher plasma prolactin values before and during the OGTT than the non-lactating women (P < 0.005). Fasting values of serum FSH, LH, progesterone and plasma glucagon were similar in the two groups. The non-lactating women had higher fasting co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Adiponectin is an adipocyte-derived protein that has been correlated with insulin sensitivity and pancreatic β-cell function and proliferation. (33) In suppressing circulating leptin and adiponectin,(34) prolactin may reduce insulin secretion and enhance sensitivity of the pancreatic β-cells. (32) Lower circulating adiponectin concentrations during lactation are unlikely to adversely affect insulin sensitivity, because glucose uptake by the mammary gland is supported by non-insulin mediated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin is an adipocyte-derived protein that has been correlated with insulin sensitivity and pancreatic β-cell function and proliferation. (33) In suppressing circulating leptin and adiponectin,(34) prolactin may reduce insulin secretion and enhance sensitivity of the pancreatic β-cells. (32) Lower circulating adiponectin concentrations during lactation are unlikely to adversely affect insulin sensitivity, because glucose uptake by the mammary gland is supported by non-insulin mediated mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Lactating compared with nonlactating women display more favorable metabolic parameters, including less atherogenic blood lipids [34], lower fasting and postprandial blood glucose and insulin [27, 28], and greater insulin sensitivity [27]. Exclusive lactation is associated with greater weight loss in some studies, and with the most favorable metabolic profiles [69].…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of a 30 % higher glucose load by lactating women resulted in similar plasma glucose despite lower insulin concentrations in lactating women [27]. Other studies have reported lower fasting plasma glucose and insulin concentrations in [28], as well as lower plasma insulin concentrations in the postabsorptive state for lactating women [29]. Hubinont et al [30] administered frequently sampled oral glucose tolerance tests (OGTT) with blood samples drawn every 15 minutes for 120 minutes.…”
Section: Blood Glucose and Insulin Sensitivitymentioning
confidence: 99%
“…Several studies conducted during or shortly after lactation have revealed that fasting blood glucose, postprandial blood glucose and insulin concentrations were lower [11,12], atherogenic blood lipid concentrations were lower [13] and insulin sensitivity was improved [11] in healthy, middle-aged lactating women compared with non-lactating women. These short-term observations may be explained by metabolic adaptions to lactogenesis, particularly the diversion of glucose by insulin-independent pathways for uptake by the mammary gland [14].…”
Section: Introductionmentioning
confidence: 99%